ENHANCING YOUNG ADULT LITERATURE TO IMPROVE READING ABILITY - AMELIA, KIKI RIZKI; NOVIA, FITRI (Linguists : Journal of Linguistics and Language Teaching, 2021)
Reading is the manner of grasping the content of a paragraph of text. Nonetheless, some students are fighting to strengthen reading comprehension. This study proposed to confirm whether Young Adult literature improved students’ reading ability in narrative text. The design of that research was used quasi-experimental. Participants were eight grade students of SMP N 1 Inderalaya Selatan Ogan Ilir South Sumatera. The instrument used was a written test that included 25 questions in multiple-choice form. T-test was used to examine the data. Independent samples t-test analysis revealed that pvalue (0.001) was lower than άvalue (0.05). This study was indicated that learners who were encouraged to read narrative literature through Young Adult Literature improved significantly. In conclusion, the students improved their reading ability better by reading extensively through Young Adult Literature.